The Effect of Salt Reduction and Partial Substitution of NaCl by KCl on Physicochemical, Microbiological, and Sensorial Characteristics and Consumers' Acceptability of Semi-Hard and Hard Lactose-Free Cow's Milk Cheeses - Juan, Bibiana; Trujillo, Antonio-José; Ferragut, Victoria (Frontiers in Nutrition, 2022)
Increasing consumer demand for healthier foods prompts the development of cheeses reduced in salt. This study was aimed to assess the effect of reducing the level of NaCl and their partial substitution by KCl on the biochemical, microbiological, sensorial and consumer’s acceptability of semi-hard and hard lactose free cow’s milk cheeses. In order to improve possible lower salty taste or development of bitter taste, the addition of yeast extract, as a flavour enhancer, was also checked. Different brining time and brine conditions were tested to obtained a reduction >25% of salt respect to conventional cheese. Reduced-salt cheeses were elaborated reducing by the half the salting time used to conventional cheeses, and 60 Na+:40 K+ were used to reduce Na concentration in substituted cheeses. The results obtained in this study show that the reduction of salt by both methods in semi-hard and hard lactose-free cheeses could be an alternative for the production of healthier and sensorial acceptable cheeses, without significantly affecting their physicochemical characteristics. The addition of yeast extract, as a flavour enhancer, increased the free amino acids levels but decreased the acceptability of cheeses.